An Isotope-labeling Study of CO2 Formation Pathways in Molecular Clouds: Ultraviolet Photolysis of CO–H2O Ice - Akemi Hirayama; Ichiro Arakawa; Koichiro Yamakawa (The Astrophysical Journal, 2023)
With the use of reflection–absorption infrared spectroscopy, we investigated the binary ice of CO and H _2 O at 10 K under ultraviolet irradiation as an analog of the interstellar ice mantle. We employed H _2 ^18 O instead of H _2 ^16 O to distinguish the formation pathways of CO _2 , and prepared mixed-ice samples under CO- and H _2 O-rich conditions as well as bilayered ice, where CO was condensed on H _2 O ice. After the ultraviolet irradiation onto any sample, we detected infrared absorption bands of C ^16 O _2 and C ^18 O ^16 O, which were generated through the CO–CO and CO–H _2 O reactions, respectively. The additional detection of C ^18 O _2 clearly indicated that the photodissociation and regeneration of CO _2 also took place in ice. We analyzed the irradiation-time dependence of the C ^16 O _2 and C ^18 O ^16 O column densities in CO-rich ice to determine the effective cross sections of the CO _2 formation through the CO–CO ( ${σ }_{{{\rm{C}}}^{16}{{\rm{O}}}_{2}}$ ) and CO–H _2 O ( ${σ }_{{{\rm{C}}}^{18}{{\rm{O}}}^{16}{\rm{O}}}$ ) reactions simultaneously: ${σ }_{{{\rm{C}}}^{16}{{\rm{O}}}_{2}}$ = 3 × 10 ^−21 cm ^2 and ${σ }_{{{\rm{C}}}^{18}{{\rm{O}}}^{16}{\rm{O}}}$ = 5 × 10 ^−18 cm ^2 . Despite the rather small value of ${σ }_{{{\rm{C}}}^{16}{{\rm{O}}}_{2}}$ compared to ${σ }_{{{\rm{C}}}^{18}{{\rm{O}}}^{16}{\rm{O}}}$ , the former reaction was found to be nonnegligible in terms of the CO _2 yield, even at the H _2 O-rich condition.